Dislocation locking in silicon by oxygen and oxygen transport at low temperatures - Senkader, S; Giannattasio, A; Falster, R; Wilshaw, P (Trans Tech Publications Ltd, 2004)
Dislocation-oxygen interactions in silicon have been studied experimentally and using numerical modelling. Experiments were performed to understand the locking of dislocations by oxygen and to measure the unlocking stress of dislocations in the temperature range 350-900degreesC for different annealing times and oxygen concentrations. Our observations revealed that the oxygen-dislocation interactions give rise to well defined regimes in locking of dislocations as a function of temperature. From the temperature dependence it was possible to deduce the oxygen-dislocation binding energy, and to estimate oxygen diffusivity in silicon. Modelling the transport of oxygen to dislocations, in connection with numerical simulations, showed that the effective diffusivity of oxygen at lower temperatures is different from normal diffusivity and can be several orders of magnitude larger, and is then dependent on oxygen concentration. Experimental measurements were made of the temperature dependence of the stress required to unlock dislocations from oxygen atoms bound to their core. These results were used, together with those concerning diffusivity and binding energy, in numerical simulations to predict the onset of plastic deformation of silicon wafers during device processing sequences.